2014
DOI: 10.3390/nu6115103
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Status in Female University Students: Iron, Zinc, Copper, Selenium, Vitamin B12 and Folate

Abstract: Young women are at an increased risk of micronutrient deficiencies, particularly due to higher micronutrient requirements during childbearing years and multiple food group avoidances. The objective of this study was to investigate biomarkers of particular micronutrients in apparently healthy young women. Female students (n = 308; age range 18–35 year; Body Mass Index 21.5 ± 2.8 kg/m2; mean ± SD) were recruited to participate in a cross-sectional study. Blood samples were obtained from participants in the faste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 56 publications
(72 reference statements)
7
37
0
3
Order By: Relevance
“… 47–49 An Australian study on young females found a similar rate to ours (11.4%), albeit using a lower threshold of 120 pmol/L. 50 As the B 12 levels fall by around 10% from preconception to early pregnancy, 19 if we extrapolate our findings, the proportion of pregnant women with B 12 levels below 150 pmol/L is likely to be much higher. More than a third of vegetarian/vegan women in our study had B 12 deficiency, which was in keeping with studies from other UK adult population 51 and elsewhere.…”
Section: Discussionsupporting
confidence: 76%
“… 47–49 An Australian study on young females found a similar rate to ours (11.4%), albeit using a lower threshold of 120 pmol/L. 50 As the B 12 levels fall by around 10% from preconception to early pregnancy, 19 if we extrapolate our findings, the proportion of pregnant women with B 12 levels below 150 pmol/L is likely to be much higher. More than a third of vegetarian/vegan women in our study had B 12 deficiency, which was in keeping with studies from other UK adult population 51 and elsewhere.…”
Section: Discussionsupporting
confidence: 76%
“…In Saudi Arabia, anemia has been reported as 54.8% in female university students [12] . This prevalence has been shown 10% with 33% of low ferritin in another research [13] , 20% in Gaze [14] and 38.1% in India [15] . Also, 55% of all university students in Noakhali, Bangladesh, have shown to have anemia, 36% of them were male [16] .…”
Section: Introductionmentioning
confidence: 84%
“…Increased demands during adolescence due to physiological changes and during pregnancy and lactation make the young women more vulnerable. In addition, food faddism and avoidance of particular food group are common in young women which increase the risk of micronutrient deficiencies [6]. This is largely unnoticed condition in this age group.…”
Section: Discussionmentioning
confidence: 99%